Comparing Grammar Translation Method and Communicative Language Teaching in EFL Context: A Qualitative Literature Review - Nisha, Paulomi Rahman (FOSTER: Journal of English Language Teaching, 2024)
Teaching English as a foreign language (EFL) differs greatly from teaching English as a first language (L1). To ensure that teaching and learning are successful and efficient, teachers must possess a broad range of pedagogical expertise. Each method needs to be adjusted to the particular educational and environmental setting. The primary objective of this article is to provide comprehensive insights into two prominent language teaching methods, namely the Grammar Translation Method (GTM) and Communicative Language Teaching (CLT). While GTM has been historically prevalent, CLT has recently gained widespread popularity. This paper focuses on the understanding of educational practitioners, particularly in the domain of English Language Teaching (ELT) setting, by conducting a comprehensive comparison of GTM and CLT thoroughly, focusing on teaching techniques, characteristics of both teaching methods, and the way the instructor addresses students’ mistakes. Although CLT is recognized as the more realistic and advantageous method in contemporary contexts, it is still acknowledged that GTM possesses certain positive attributes. Additionally, since every country has its own unique set of circumstances, social norms, and background, the teacher must be aware of the most suitable teaching-learning method.